Analysis Variation of Concentration and Pickling Time in SA-312 304 on Oxide Layer Thickness - Kusminah, Imah Luluk; Pratiwi, Wiwik Dwi; Hermansyah, Aditya; Anggara, Dika; P, Widya Emilia (International Journal of Marine Engineering Innovation and Research, 2025)
Austenitic stainless steel SA-312 Grade 304 offers good corrosion resistance, but welding can form oxide layers that degrade its performance. Pickling with nitric acid (HNO3) and hydrofluoric acid (HF) is commonly used to remove oxides and restore corrosion resistance. This study examines the effects of varying HNO3 concentration and pickling time on oxide layer thickness. Optical and scanning electron microscopy (SEM) were performed. The optimal result was achieved with 15% HNO3 + 4% HF for 35 minutes, producing a 5.6658 µm oxide layer, while 25% HNO3 + 4% HF for 35 minutes yielded only 3.0082 µm. Results show that proper pickling parameters effectively reduce oxide scale.